Mental health of expectant mothers during the COVID-19 pandemic : comparison of anxiety and depressive scores of expectant mothers in Iceland on the 16. week of pregnancy before and during COVID-19 - Eygló Ósk Gústafsdóttir 1995- (2023)
The COVID-19 pandemic had a big impact on society across the world and was shown to have a negative effect on mental health amongst the general public and pregnant women. The pandemic did not impact Iceland as greatly as in many other nations across the world, and no negative effect is found of the pandemic on mental health in the general public in Iceland. The aim of this study was to determine if the COVID-19 pandemic had a negative effect on depressive- and anxiety symptoms in pregnant women, and to determine if the pandemic had a greater negative effect on primipara women and women of foreign origin than other pregnant women. Participants in this study were pregnant women who attended the antenatal care in their 16th week of pregnancy from the years 2018-2021 at their Primary Health Care clinic in the Capital Area and answered the screening lists EPDS and GAD-7 (N= 7294). The data was analysed with One-way between subject ANOVA, a factorial ANOVA and finally with an independent t-test. Results indicate that the COVID-19 pandemic did not have a significant effect on depressive- and anxiety scores in pregnant women in general, and that did not differ for primipara women and women of foreign origin. Primipara women had significantly higher levels of depression and anxiety symptoms than multipara women. Additionally, women who answered the screening lists in a language other than Icelandic had significantly higher levels of symptoms than Icelandic women. That highlights the importance of improved services for this minority group and additional research to identify risk factors among this group. Keywords: Antenatal care, Anxiety, Depression, Pregnant women COVID-19 heimsfaraldurinn hafði mikil áhrif á samfélagið í heiminum og rannsóknir sýna að heimsfaraldurinn hafði neikvæð áhrif á andlega heilsu almennings og verðandi mæðra. Heimsfaraldurinn hafði ekki jafn mikil áhrif á Íslandi og í mörgum löndum erlendis, en engin neikvæð áhrif fundust af heimsfaraldrinum á andlega heilsu almennings á Íslandi. Markmið ...